Analysis of systemic inflammatory biomarkers in neuroendocrine carcinomas of the lung: prognostic and predictive significance of NLR, LDH, ALI, and LIPI score. (August 2020) - Galvano, Antonio; Peri, Marta; Guarini, Aurelia Ada; Castiglia, Marta; Grassadonia, Antonino; De Tursi, Michele; Irtelli, Luciana; Rizzo, Sergio; Bertani, Alessandro; Gristina, Valerio; Barraco, Nadia; Russo, Antonio; et al.
Background: Lung neuroendocrine carcinoma (NEC) is characterized by aggressive clinical behavior and lack of treatment advances. We evaluate the prognostic and the predictive roles of systemic inflammatory biomarkers in patient circulating blood: neutrophil–lymphocyte ratio (NLR), lactate dehydrogenase (LDH), advanced lung cancer inflammation index (ALI), and the Lung Immune Prognostic Index (LIPI) score. Methods: A total of 120 patients with small-cell lung cancer (SCLC) ( n = 110) and large cell neuroendocrine carcinoma (LCNEC) ( n = 10) were enrolled. Overall survival (OS) was evaluated by Kaplan–Meier estimator and univariate and multivariate Cox proportional hazard analyses were performed to determine prognostic factors associated with OS while χ 2 test was used for categorical data. Results: NLR cutoff value was 1.93. NLR was measured before and after first-line chemotherapy; 25 (21%) patients had higher NLR (delta NLR >1), whereas NLR was lower in 37 (31%). At the univariate analysis, median OS was 12 months: OS for SCLC and LCNEC were 11 months and 14 months, respectively. OS had a prognostic positive value in patients with pre-treatment NLR <1.93 ( p = 0.0002), LDH <600 U/L ( p = 0, 03) and ALI ⩾34 ( p = 0, 0065). At the multivariate analysis, Eastern Cooperative Oncology Group performance status, LDH levels and response after first-line chemotherapy were independently associated with OS. Median OS for good, intermediate, and poor LIPI was 15 months, 11 months, and 9 months, respectively( p = 0.091). Patients with higher NLR (>1.93) had an increased probability of tumor progression ( p = 0.045, χ 2 test). Conclusion: This study demonstrated that systemic inflammatory biomarkers could facilitate the understanding of survival differences in the clinical management of lung NEC patients, underlying the need for prospective biomarker-driven studies in the immune checkpoint inhibitors setting.